Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

A Novel Mitochondrial-Related Gene Signature for the Prediction of Prognosis and Therapeutic Efficacy in Lower-Grade Glioma - Jingyi Yang; Lei Shen; Jiabin Zhou; Ji Wu; Chuqiao Yue; Tiansheng Wang; Songshan Chai; Yuankun Cai; Dongyuan Xu; Yu Lei; Jingwei Zhao; Yixuan Zhou; et al. (Biochemical Genetics, 2025)

International law concerning the environmental protection in Arctic: what is left behind UNCLOS and the BBNJ Agreement? - Fangling Wu; Tiansheng Li (Frontiers in Marine Science, 2025)
The Arctic region, with its unique and fragile ecosystem, faces significant challenges in environmental protection due to climate change, increasing human activities, and geopolitical tensions. This paper examines the international legal framework governing Arctic environmental protection, focusing on the roles and limitations of the United Nations Convention on the Law of the Sea (UNCLOS) and the Agreement on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement). While UNCLOS provides a foundational legal framework for ocean governance, its applicability in addressing Arctic environmental concerns should be acknowledged, as should the complementary role of the BBNJ Agreement. However, the lack of provisions specific to Arctic environmental issues creates a gap between the effectiveness of international law and the urgent need for a comprehensive legal regime tailored to the Arctic context. Furthermore, the supplementary role of the BBNJ Agreement to UNCLOS remains limited. By highlighting key challenges in the implementation of international law, including disputes over Article 234 of UNCLOS, this study underscores the urgent need for a more robust and cohesive international legal approach to ensure the sustainable future of the Arctic environment, and concludes with appropriate recommendations.

Mechanism of cadmium (Cd) enrichment in the soil of karst areas with high geochemical background in Southwest China - Bo Li; Kun Lin; Xu Liu; Xudong Ma; Xuezhen Li; Zhiliang Wu; Cheng Li; Tao Yu; Tiansheng Wu; Zhongfang Yang (Chemical Geology, 2025)

Improved mapping of heavy metals in agricultural soils using machine learning augmented with spatial regionalization indices - Xudong Ma; Dong-Xing Guan; Chaosheng Zhang; Tao Yu; Cheng Li; Zhiliang Wu; Bo Li; Wenda Geng; Tiansheng Wu; Zhongfang Yang (Journal of Hazardous Materials, 2024)

CCUS-assisted electricity-chemical polygeneration system for decarburizing coal-fired power plant: Process integration and performance assessment - Leiyu Zhang; Zongyue Tang; Ruxing Gao; Ying Wu; Lei Wang; Chundong Zhang; Ki-Won Jun; Seok Ki Kim; Tiansheng Zhao; Hui Wan; Guofeng Guan (Journal of Cleaner Production, 2024)

Spatially varying relationships of soil Se concentration and rice Se concentration in Guangxi, China: A geographically weighted regression approach - Bo Li; Xu Liu; Chaosheng Zhang; Tao Yu; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Lei Wang; Kun Lin; Xudong Ma; Xuezhen Li; Husheng Zhang; et al. (Chemosphere, 2023)

Identification of the spatial patterns and controlling factors of Se in soil and rice in Guangxi through hot spot analysis - Xu Liu; Chaosheng Zhang; Tao Yu; Wenbing Ji; Tiansheng Wu; Xiaoxiong Zhuo; Cheng Li; Bo Li; Lei Wang; Yuxiang Shao; Kun Lin; Xudong Ma; et al. (Environmental Geochemistry and Health, 2023)

Identification of high ecological risk areas with naturally high background value of soil Cd related to carbonate rocks - Xu Liu; Tao Yu; Chaosheng Zhang; Cheng Li; Bo Li; Zhongfang Yang; Qiong Yang; Yiren Duan; Wenbing Ji; Tiansheng Wu; Lei Wang (Environmental Geochemistry and Health, 2023)

miR-24-3p Regulates Epithelial–Mesenchymal Transition and the Malignant Phenotype of Pancreatic Adenocarcinoma by Regulating ASF1B Expression - Wentao Huang; Tiansheng Lin; Long Huang; Junyi Wu; Jiaming Hong; Funan Qiu; Yifeng Tian; Yaodong Wang (Biochemical Genetics, 2023)
Anti-silencing function protein 1 homolog B (ASF1B) has been implicated in the occurrence and development of cancers. The present work explored the functional role and the expression regulation of ASF1B in pancreatic ductal adenocarcinoma (PDAC). Based on the real-time quantitative PCR (qRT-PCR) and immunohistochemistry (IHC), ASF1B was significantly upregulated in PDAC tissues. High expression of ASF1B was associated with a poor overall survival (OS) and recurrence-free survival (DFS) in the PDAC patients. ASF1B also showed a relatively higher expression in PDAC cells (AsPC-1, PANC-1) when compared with human pancreatic ductal epithelial cells (HPDFe-6). CCK8 and clone formation assay demonstrated that silencing ASF1B impaired the proliferation in PANC-1 and AsPC-1 cells, and Annexin V-PI staining showed an increased level of apoptosis upon ASF1B silencing. ASF1B silencing also suppressed the migration and invasion in PDAC cells, as revealed by Transwell assays. We further showed that miR-24-3p was downregulated in PDAC tissues and cells, which functionally interacted with ASF1B by dual-luciferase reporter assay. miR-24-3p negatively regulated ASF1B expression to modulate the malignant phenotype of PDAC cells. ASF1B shows high expression in PDAC, which promotes the malignancy and EMT process of PDAC cells. miR-24-3p is a negative regulator of ASF1B and is downregulated in PDAC cells. Our data suggest that targeting ASF1B/miR-24-3p axis may serve as an intervention strategy for the management of PDAC.

Degradation of vinyl ester resin and its composites via cleavage of ester bonds to recycle valuable chemicals and produce polyurethane - Ning Zhang; Xiaojing Cui; Chizhou Wang; Shaodi Wu; Yuhua Zhao; Yongqin Qi; Xianglin Hou; Haibo Jin; Tiansheng Deng (Waste Management, 2023)

Ecological risk assessment of Cd and other heavy metals in soil-rice system in the karst areas with high geochemical background of Guangxi, China - Qiong Yang; Zhongfang Yang; Qizuan Zhang; Xu Liu; Xiaoxiong Zhuo; Tiansheng Wu; Lei Wang; Xueji Wei; Junfeng Ji (Science China Earth Sciences, 2021)

Potential Ecological Risk Assessment of Heavy Metals in the Fe–Mn Nodules in the Karst Area of Guangxi, Southwest China - Wenbing Ji; Zhongfang Yang; Tao Yu; Qiong Yang; Yubo Wen; Tiansheng Wu (Bulletin of Environmental Contamination and Toxicology, 2021)

Characterization of HIV-1 subtypes and transmitted drug resistance among treatment-naive HIV-infected individuals in Zhejiang, China, 2014-2017 - Yufan Xu; Xiaorong Peng; Xiuming Peng; Shujing Ji; Bin Chen; Liyan Wang; Xiangyun Lu; Tiansheng Xie; Tao Sun; Hui Wang; Nanping Wu (Archives of Virology, 2018)

High-throughput sequencing identifies HIV-1-replication- and latency-related miRNAs in CD4+ T cell lines - Xiangyun Lu; Jin Yang; Haibo Wu; Zongxing Yang; Changzhong Jin; Juan Wang; Linfang Cheng; Xiaorong Peng; Fumin Liu; Xiuming Peng; Sujing Ji; Huilin Ou; et al. (Archives of Virology, 2017)

Isolation and genetic characterization of novel reassortant H6N6 subtype avian influenza viruses isolated from chickens in eastern China - Haibo Wu; Rufeng Lu; Xiuming Peng; Xiaorong Peng; Linfang Cheng; Changzhong Jin; Xiangyun Lu; Tiansheng Xie; Hangping Yao; Nanping Wu (Archives of Virology, 2016)

Molecular characterization of a novel reassortant H1N2 influenza virus containing genes from the 2009 pandemic human H1N1 virus in swine from eastern China - Xiuming Peng; Haibo Wu; Lihua Xu; Xiaorong Peng; Linfang Cheng; Changzhong Jin; Tiansheng Xie; Xiangyun Lu; Nanping Wu (Virus Genes, 2016)

Multiple amino acid substitutions involved in the adaptation of avian-origin influenza A (H10N7) virus in mice - Haibo Wu; Xiuming Peng; Xiaorong Peng; Linfang Cheng; Changzhong Jin; Xiangyun Lu; Tiansheng Xie; Hangping Yao; Nanping Wu (Archives of Virology, 2016)

Genetic characterization of natural reassortant H4 subtype avian influenza viruses isolated from domestic ducks in Zhejiang province in China from 2013 to 2014 - Haibo Wu; Xiuming Peng; Xiaorong Peng; Linfang Cheng; Xiangyun Lu; Changzhong Jin; Tiansheng Xie; Hangping Yao; Nanping Wu (Virus Genes, 2015)

Characterization of a novel highly pathogenic H5N2 avian influenza virus isolated from a duck in eastern China - Haibo Wu; Xiaorong Peng; Lihua Xu; Changzhong Jin; Linfang Cheng; Xiangyun Lu; Tiansheng Xie; Hangping Yao; Nanping Wu (Archives of Virology, 2014)